Enhanced gut barrier integrity sensitizes colon cancer to immune therapy. (2nd November 2018) - Bhutiani, Neal; Li, Qingsheng; Anderson, Charles D.; Gallagher, Heather C.; De Jesus, Magdia; Singh, Rajbir; Jala, Venkatkrishna R.; Fraig, Mostafa; Gu, Tao; Egilmez, Nejat K.
ABSTRACT: Oral IL-10 suppressed tumor growth in the APC min/+ mouse/ Bacteroides fragilis colon cancer model while a similar formulation of IL-12 exacerbated disease. In contrast, combined treatment with IL-10 and IL-12 resulted in near-complete tumor eradication and a significant extension of survival. The cytokines mediated distinct immunological effects in the gut, i.e. IL-10 diminished Th17 cell prevalence whereas IL-12 induced IFNγ and enhanced CD8 + T-cell activity. Loss-of-function studies demonstrated that IL-12-driven CD8 + T-cell expansion was only partially responsible for the synergy, and that both the detrimental and the beneficial activities of IL-12 required IFNγ. Examination of colon physiology in mice receiving single vs dual treatment revealed that exacerbation of disease by IL-12 monotherapy was associated with compromised gut barrier integrity whereas combined treatment reversed this effect, uncovering additional activity by the cytokines on the stroma. Further analysis showed that the stromal effects of IL-12 included a 6-fold increase in IL-10RA expression in the colon epithelium, linking the epithelial activity of the cytokines. Finally, dual but not monotherapy induced a 3-fold increase in tight junction protein levels in the colon, identifying the mechanism by which IL-10 blocked the detrimental effect of the IL-12-IFNγ axis on barrier function without interfering with its beneficial immunological activity. These findings establish that the synergy between IL-12 and IL-10 was mediated by pleiotropic effects on the immune and the non-immune compartments and that the latter activity was critical to therapeutic outcome.